Borealization of the Arctic Ocean in Response to Anomalous Advection From Sub-Arctic Seas - Polyakov, Igor V.; Alkire, Matthew B.; Bluhm, Bodil A.; Brown, Kristina A.; Carmack, Eddy C.; Chierici, Melissa; Danielson, Seth L.; Ellingsen, Ingrid; Ershova, Elizaveta A.; Gårdfeldt, Katarina; Ingvaldsen, Randi B.; Pnyushkov, Andrey V.; et al. (Frontiers in Marine Science, 2020)
An important yet still not well documented aspect of recent changes in the Arctic Ocean is associated with the advection of anomalous sub-Arctic Atlantic- and Pacific-origin waters and biota into the polar basins, a process which we refer to as borealization. Using a 37-year archive of observations (1981–2017) we demonstrate dramatically contrasting regional responses to atlantification (that part of borealization related to progression of anomalies from the Atlantic sector of sub-Arctic seas into the Arctic Ocean) and pacification (the counterpart of atlantification associated with influx of anomalous Pacific waters). Particularly, we show strong salinification of the upper Eurasian Basin since 2000, with attendant reductions in stratification, and potentially altered nutrient fluxes and primary production. These changes are closely related to upstream conditions. In contrast, pacification is strongly manifested in the Amerasian Basin by the anomalous influx of Pacific waters, creating conditions favorable for expansion of Pacific species into the Arctic interior and increased heat and freshwater content in the Beaufort Gyre halocline. Here, changes in the upper (overlying) layers are driven by local Arctic processes resulting in stronger wind/ice/ocean coupling, increased convergence within the Beaufort Gyre, a thickening of the fresh surface layer, and a deepening of the nutricline and deep chlorophyll maximum. Thus, a divergent (Eurasian Basin) gyre responds altogether differently than does a convergent (Amerasian Basin) gyre to climate forcing. Available geochemical data indicate a general decrease in nutrient concentrations Arctic-wide, except in the central Arctic and northern Chukchi Sea and Canada Basin. Thus, changes in the circulation pathways of specific water masses, as well as the utilization of nutrients in upstream regions, may control the availability of nutrients in the Arctic Ocean. Model-based evaluation of the trajectory of the Arctic climate system into the future suggests that Arctic borealization will continue under scenarios of global warming. Results from this synthesis further our understanding of the Arctic Ocean’s complex and sometimes non-intuitive Arctic response to climate forcing by identifying new feedbacks in the atmosphere-ice-ocean system in which borealization plays a key role.